Prinsip-Prinsip Montessori dalam Pembelajaran Anak Usia Dini di Ra Shazia Palembang - Melinda Puspita Sari Jaya; viana; Syarwani Ahmad (DIAJAR: Jurnal Pendidikan dan Pembelajaran, 2022)
The purpose of this study was to find out how Montessori principles were applied in the learning of group B children at RA Shazia, and to find out what obstacles were encountered in applying Montessori principles to the learning of group B children at RA Shazia Palembang. This research was conducted at RA Shazia Palembang. Informants in this study consisted of principals, homeroom teachers, teachers and parents of students of RA Shazia Palembang. The type of research in this thesis is qualitative research. Data collection techniques in the form of observation, interviews, and documentation. This research is based on the results of problem identification through interview, observation and documentation methods. Based on the data obtained from interviews and observations, it shows that the application of the principles of the Montessori Method in early childhood learning has not gone well, in the field application there are still many obstacles. From the three informants who have been interviewed and the observation stage carried out in each class at RA Shazia Palembang, RA Shazia's teachers have not fully adopted the teaching procedures from the principles of the Montessori method so that the learning process is still conventional.